The influence of financial attitude, perceived ease of use of fintech with financial literacy as a mediating variable on the financial management behavior of new students in Surabaya. - Melisa Jamiatun; R. A. Sista Paramita (Universitas Negeri Surabaya, 2025)
Good financial management in a person can help achieve financial stability. This study aims to determine and analyze the influence of financial attitudes, perceived ease of use of fintech on financial management behavior, with financial literacy as a mediating variable. This study uses quantitative methods. The sampling technique used is non-probability sampling with purposive sampling, involving 164 respondents. The data in this study were analyzed using Structural Equation Modeling (SEM) with the help of SmartPLS 4.1.1.2 software. The results of the study prove that financial attitudes and financial literacy influence financial management behavior using the TPB theory. Then the TAM theory has proven that perceived ease of use also influences financial management behavior and financial literacy. Meanwhile, the TPB theory has not been able to prove that financial attitudes have a positive effect on financial literacy and cannot prove that financial literacy is able to mediate financial attitudes towards financial management behavior. While the TAM theory is able to prove that financial literacy is able to mediate the influence of perceived ease of use of fintech on financial management behavior.